"This paper is Stanislavskian-based" – an examination of actor training and practice in English Canada. Issue 1 (2nd January 2017) - Julien, Martin
Abstract: Throughout English Canada, a variety of methodologies based on Stanislavski's "system" have been the centrepieces for actor training at a majority of colleges and universities for decades. Far from being a calculated pedagogical gambit, this practically unquestioned aquiescence to a pre-professional psychophysical training framework that consists of early Stanislavskian concepts such as "emotion memory", "given circumstances" and the "magic if" has developed as a default response to hegemonic notions regarding the "marketplace" and a "common language". The potential ramifications of this situation are examined, with specific reference to similar practices in the UK and the US.